2005
DOI: 10.1007/s00330-005-2903-x
|View full text |Cite
|
Sign up to set email alerts
|

Gray-scale three-dimensional sonography of thyroid nodules: feasibility of the method and preliminary studies

Abstract: The aim of the study was differential evaluation of new and classical sonographic features of benign thyroid nodules and thyroid cancer with three-dimensional gray-scale sonography and evaluation of the effectiveness of the thin-slice surface rendered images in comparison with multiplanar reformation (MPR) presentation. Fifty-four thyroid nodules were interactively evaluated with thin-slice smooth surface rendering: shape in the c-plane (parallel to the probe) and evaluation of echogenicity, margins and calcif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…In this study, US was shown to be a sensitive method for the detection of recurrent or persistent thyroid disease in patients with total thyroidectomies and it can be used safely as an effective monitoring tool in patients with even minimal thyroid remnant. One study reported that either 2D or 3D US images are effective and sensitive methods for the evaluation of thyroid nodules (7). However, in our study, thyroid scintigraphy and uptake measurement were more sensitive diagnostic tests than US for the detection of thyroid remnant, especially for minimal thyroid remnant in the thyroid bed that is clinically negligible.…”
Section: Discussioncontrasting
confidence: 49%
“…In this study, US was shown to be a sensitive method for the detection of recurrent or persistent thyroid disease in patients with total thyroidectomies and it can be used safely as an effective monitoring tool in patients with even minimal thyroid remnant. One study reported that either 2D or 3D US images are effective and sensitive methods for the evaluation of thyroid nodules (7). However, in our study, thyroid scintigraphy and uptake measurement were more sensitive diagnostic tests than US for the detection of thyroid remnant, especially for minimal thyroid remnant in the thyroid bed that is clinically negligible.…”
Section: Discussioncontrasting
confidence: 49%
“…[21][22][23][24] However, there are few studies of observer variability in thyroid US except for some reports about the volume of thyroid nodules. [25][26][27] The current study showed a relatively high degree of consistency among multiple observers in US evaluation of thyroid nodules. The characteristic of internal content (solid versus cystic) showed substantial agreement, and the shape, echogenicity, calcification, and diagnostic categories showed moderate agreement.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note the anatomic landmarks, position the patient supine with the neck extended, and examine the entire region from the sternal notch to the chin and bilaterally to include both node-bearing regions. Newly developed threedimensional thyroid ultrasound may have a role in the evaluation of new nodular masses arising in patients with nodular goiter or other complex thyroid histologies [48,49], but is not widely available.…”
Section: Diagnostic Thyroid Ultrasoundmentioning
confidence: 99%